A study on the public attention in the Belt and Road Initiative - Hu Liusho; Hu Jian; Wang Mingyu (SHS Web of Conferences, 2023)
This paper constructs residents’ attentiveness index of the Belt and Road Initiative by big data, and combines social and economic factors to study the spatial and temporal distribution of initiative attentiveness, we can find that (1) the attentiveness of the initiative will be greatly affected by large government conferences, and there is a mismatch between the areas covered by the initiative and the areas. (2) both per capita GDP and the proportion of fiscal investment in GDP have a significantly positive impact on the initiative attentiveness of residents, while CPI has a significantly negative Population size and unemployment rates do not have a significant impact on the initiative’s attentiveness. (3) the impact of initiative attentiveness has obvious regional differences. This paper breaks the habitual cognition of the attention of the initiative, and combines the social and economic conditions, and puts forward some suggestions, such as expanding the boundary of the Belt and Road, taking multiple measures to mobilize the social forces to build the Belt and Road, and treating the different policies.